Insights into thrombin activatable fibrinolysis inhibitor function and regulation. (30th June 2013) - Foley, J. H.; Kim, P. Y.; Mutch, N. J.; Gils, A.
Summary: Fibrinolysis is initiated when the zymogen plasminogen is converted to plasmin via the action of plasminogen activators. Proteolytic cleavage of fibrin by plasmin generates C‐terminal lysine residues capable of binding both plasminogen and the plasminogen activator, thereby stimulating plasminogen activator‐mediated plasminogen activation and propagating fibrinolysis. This positive feedback mechanism is regulated by activated thrombin activatable fibrinolysis inhibitor (TAFIa), which cleaves C‐terminal lysine residues from the fibrin surface, thereby decreasing its cofactor activity. TAFI can be activated by thrombin alone, but the rate of activation is accelerated when in complex with thrombomodulin. Plasmin is also known to activate TAFI. TAFIa has no known physiologic inhibitors and consequently, its primary regulatory mechanism involves its intrinsic thermal instability. The rate of TAFI activation and stability of the active form, TAFIa, function in maintaining its concentration above the threshold value required to down‐regulate fibrinolysis. Although all methods to quantify TAFI or TAFIa have their limitations, epidemiologic studies have indicated that elevated TAFI levels are correlated with an increased risk of venous thrombosis. Major efforts have been made to develop TAFI inhibitors that can either directly interfere with TAFIa activity or impair its activation. However, the anti‐inflammatory properties of TAFIa might complicate the development and application of a TAFIa inhibitor that aims to increase the efficiency of thrombolytic therapy.